Embraced by the Spirit: the untold blessings of intimacy with God - Swindoll, Charles R. (Zondervan, 2010)
Introduction -- Who is the Holy Spirit? -- Why do I need the Spirit? -- What does it mean to be filled with the Spirit? -- How do I know I'm led by the Spirit? -- How does the Spirit free me from sin? -- Can I be prompted by the Spirit today? -- Does the Spirit heal today? -- How can I experience the power of the Spirit?